Development and planning of measures to reduce the risk of the foot-and-mouth disease virus spread (case of the Republic of Kazakhstan) - Kairat Turgenbayev; Aida Abdybekova; Assiya Borsynbayeva; Vladimir Kirpichenko; Aiken Karabassova; Yerzhan Ospanov; Saltanat Mamanova; Perizat Akshalova; Elvira Bashenova; Saira Kaymoldina; Marat Turkeev; Bakhit Tulepov (Caspian Journal of Environmental Sciences)
The current epizootic situation of foot-and-mouth disease (FMD) in the world indicates the need to organize measures for its prevention and elimination among agricultural and wild animals. The present study aimed to develop and plan measures to reduce the risk of spreading FMD virus in Kazakhstan. In epizootiological studies, the authors used the periodic bulletins of the World Organization for Animal Health, statistical data on the epizootic situation of FMD in Kazakhstan, geographical data of the territories of the regions of Kazakhstan included in the zones with vaccination and acceptable FMD status, and other necessary information. FMD monitoring was carried out by serological and virological studies of blood serum samples by detecting antibodies to the nonstructural protein of FMD virus and the reproductive pathogen or its antigenic components. According to the results of epizootiological monitoring, serological studies established the highest sero-positivity (25.3%) in cattle during 2021. Repeated virological studies of samples from these animals did not established signs of the presence and persistent circulation of FMD virus. However, in 2022, a case of FMD was recorded in the Karaganda region of Kazakhstan in the zone without vaccination. It was found that the immunogenicity of FMD vaccine among vaccinated cattle, goats and sheep was 85% or higher. However, the intensity of post-vaccination immunity persisted for about 3 months, instead of the 6 months guaranteed by the manufacturer. The extensive type of animal husbandry did not reduce the threats of the spread of FMD virus. The authors have identified logistics corridors through which the penetration and spread of FMD virus is possible. It is not possible to minimize the threat of spread using vaccination alone. Therefore, the authors have developed measures that include elements of biosecurity, surveillance and rapid diagnostics, animal movement control, and international cooperation.